Behavioral Changes in Accessing Outpatient Care During the Covid-19 Pandemic - Hasanah, Alfiah; Hardiawan, Donny; Marrosa, Jefani; Ramadhan, Adlan; Heriyaldi, Heriyaldi; Sihaloho, Estro Dariatno; Siregar, Adiatma Y. M. (UI Scholars Hub, 2021)
Unwillingness to seek healthcare has been observed in citizens from many countries during the Covid-19 pandemic. Previous studies show that the changes in behavior are due to various reasons such as economic slowdown, loss of health insurance due to termination of employment, and fear of contracting the virus. This behavior may result in worsened health conditions, making a individual more susceptible to the virus. The supply side of health care is one of the things that should be considered in the discussion about access to health care in developing countries. This paper investigates access to the healthcare problem of Indonesians, discusses both the supply side and demand side by looking at the change of behavior due to the patients’ fear of getting treatment during pandemic covid-19. We will serve this purpose through a small-scale survey and offer some insights from a statistical analysis perspective as well. Based on a survey from 588 respondents from the west Indonesia region, this study observes that the respondents’ health condition shows no significant change before and during the Covid-19 pandemic era. On the other hand, the respondents’ frequency of accessing outpatient healthcare proves to be significantly decreasing during the Covid-19 pandemic era, with 23,4% of the respondents stating that they avoid utilizing outpatient healthcare as an effort to avoid the Coronavirus. The frequency of using Kartu Indonesia Sehat to access outpatient healthcare also shows a significant decrease during this pandemic era.